Efficient OER nanocomposite electrocatalysts based on Ni and/or Co supported on MoSe2 nanoribbons and MoS2 nanosheets - Bibiana K. Martini (Elsevier, 2022)
It is well known that the benchmark electrocatalysts for OER in alkaline solution are RuO2 and IrO2; however, the high cost, scarcity, and instability of these metal oxides impede their ample use in OER processes, and this has fueled the search for cheap Earth-abundant elements which are equally efficient for application as electrocatalysts in OER. The present work reports the use of hydrothermal and calcination methods for the synthesis of nanocomposites made up of Ni and/or Co salts and urea in combination with MoSe2 and MoS2 and their application as efficient and stable electrocatalysts for OER in alkaline solution. The NiCoMoSe, NiCoMo, CoMoSeS, and CoMo nanocomposites constructed in the present study presented high OER electrocatalytic activity and stability mainly as a result of the following: the combination of N atoms bonded to Ni and/or Co (and Mo); the electrons released from the oxidation of Co from the 2+ to 3+state, Ni oxidation from the 2+ to 3+state, and Mo oxidation from the 4+ to 6+state; and the metal oxides (CoMoO4, NiCo2O4, Co2Mo3O8, and Co3O4) supported on MoS2 nanosheets and MoSe2 nanoribbons which contributed to a decrease in charge transfer resistance, apart from keeping the ECSA values relatively low.